Mixed-doped lithium nickel vanadate as cathode material by wet chemistry and polymer precursor method - Ismail, L.; Ramesh, S.; Tan, W.; Arof, Abdul Kariem (2009)
The mix doped LiNit_xMnx V04 (0 « x « 1) have been synthesized by using soft chemistry and polymer precursor method. XRD, TGAlDTGA and SEM analysis have been carried out to study the structural and physical properties of the samples as cathode material for Iithium ion batteries. Citric acid was added during the sample preparation as the chelating agent. SEM images showed that the grain size of the composite sample increased as the temperature was increased. The prepared samples have been characterized thermally by TGA/DTGA results.